Parenting in the Face of Trauma: Music Therapy to Support Parent–Child Dyads Affected by War and Displacement - Tamar Hadar (Children, 2024)
Background: The literature highlights the profound psychological impact of war on children, families, and communities, emphasizing the prevalence of Post-Traumatic Stress Disorder (PTSD), anxiety, and other symptoms among affected individuals. Interventions, such as Child-Parent Psychotherapy (CPP) and music therapy, show promise in mitigating trauma effects, underscoring the need for holistic approaches that address familial and community dynamics alongside individual well-being. Methods: Aiming to explore the influences of dyadic music therapy sessions on parents’ capacity to support their children, this study involved four families displaced from their home-kibbutz as result of a terrorist attack. All dyads participated in music therapy sessions with a focus on parent–child interactions and trauma processing (CPP informed). Embedded in a qualitative, phenomenological approach, the research utilized interpretative phenomenological analysis (IPA) and micro-analytic methods to explore meaningful moments in the music therapy sessions. Results: Findings identified four central categories: (1) Discovering the child’s grounding song: identifying resources; (2) Musical improvisation sets the grounds for parent–child mutual recognition of the child’s traumatic experience; (3) Musical performance empowers child and parent; (4) A sense of agency is gained through controlling the musical environment. Conclusions: The significance of restoring the children’s freedom of play, the parents’ sense of competency, and of enhancing families’ capacity to connect to their traumatic experiences through the musical environment is discussed.